CT after interhospital transfer in acute ischemic stroke: Imaging findings and impact of prior intravenous contrast administration - Mueller, Franziska; Fabritius, Matthias P.; Stueckelschweiger, Lena; Kiesl, Sophia; Moench, Sebastian; Tiedt, Steffen; Rémi, Jan; Kellert, Lars; Herzberg, Moriz; Küpper, Clemens; Dimitriadis, Konstantinos; Ricke, Jens; et al. (Frontiers in Neurology, 2022)
Objectives Large vessel occlusion (LVO) stroke patients routinely undergo interhospital transfer to endovascular thrombectomy capable centers. Imaging is often repeated with residual intravenous (IV) iodine contrast at post-transfer assessment. We determined imaging findings and the impact of residual contrast on secondary imaging. Anterior circulation LVO stroke patients were selected out of a consecutive cohort. Directly admitted patients were contrast naïve, and transferred patients had previously received IV iodine contrast for stroke assessment at the referring hospital. Two independent readers rated the visibility of residual contrast on non-contrast computed tomography (CT) after transfer and assessed the hyperdense vessel sign. Multivariate linear regression analysis was used to investigate the association of the Alberta Stroke Program Early CT score (ASPECTS) with prior contrast administration, time from symptom onset (TFSO), and CTP ischemic core volume in both directly admitted and transferred patients. Results We included 161 patients, with 62 (39%) transferred and 99 (62%) directly admitted patients. Compared between these groups, transferred patients had a longer TFSO-to-imaging at our institution (median: 212 vs. 75 min, p < 0.001) and lower ASPECTS (median: 8 vs. 9, p < 0.001). Regression analysis presented an independent association of ASPECTS with prior contrast administration (β = −0.25, p = 0.004) but not with TFSO (β = −0.03, p = 0.65). Intergroup comparison between transferred and directly admitted patients pointed toward a stronger association between ASPECTS and CTP ischemic core volume in transferred patients (β = −0.39 vs. β = −0.58, p = 0.06). Detectability of the hyperdense vessel sign was substantially lower after transfer (66 vs. 10%, p < 0.001). Conclusion Imaging alterations due to residual IV contrast are frequent in clinical practice and render the hyperdense vessel sign largely indetectable. Larger studies are needed to clarify the influence on the association between ASPECTS and ischemic core.